Shadowing Kishor on his Waste-Picking Route in Vijayawada - Prasanna Subramanya Saligram (My University, 2020)
The photoessay is an immersive and reflective exercise that attempts to understand the daily lives of waste pickers through documenting "a day in life" of Kishor, a waste picker in Vijayawada. The essay takes us through daily routine life of a waste picker, highlights occupational health hazards of waste seggregation and waste picking and the precarious working and living conditions of waste pickers.
Photoessay- that captures a "a day in life" of Kishor a waste picker in Vijayawada. Available at-https://www.ariseconsortium.org/shadowing-kishore/
Keywords: Waste Pickers